2013
DOI: 10.1016/j.jpedsurg.2013.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of upstream and downstream transforming growth factor-β transcripts in livers of children with biliary atresia and fibrogenic gene signatures

Abstract: INTRODUCTION Our previous work demonstrated that the transforming-growth factor (TGF) β pathway plays a central role in the liver fibrosis associated with experimental biliary atresia (BA). To confirm these findings in humans, we performed an in silico analysis of publicly available microarray data from liver specimens from children with BA, with the hypothesis that the TGF β pathway would be dysregulated. METHODS We analyzed publicly available liver gene expression microarray data from 47 infants with BA. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
(39 reference statements)
2
19
0
Order By: Relevance
“…In rhesus rotavirus infected rats, an animal model of BA, liver expression of MMP‐7 is increased . In several previous studies, hepatic gene expression of MMP‐7 has been shown to be upregulated both at the time of PE and LTx, implicating its potential role in liver fibrogenesis in BA . It should be emphasized that at these extreme stages of the disease the majority of patients are severely cholestatic.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In rhesus rotavirus infected rats, an animal model of BA, liver expression of MMP‐7 is increased . In several previous studies, hepatic gene expression of MMP‐7 has been shown to be upregulated both at the time of PE and LTx, implicating its potential role in liver fibrogenesis in BA . It should be emphasized that at these extreme stages of the disease the majority of patients are severely cholestatic.…”
Section: Discussionmentioning
confidence: 97%
“…MMP-7 has been shown to be upregulated in liver and lung fibrosis, and studies with a selective MMP-7 inhibitor isofraxidin have been promising in counteracting progression of fibrosis [14][15][16][17]. Previous studies have shown significant alterations in hepatic expression and serum levels of MMPs and their inhibitors in BA patients at the time of PE and LTx [15,[18][19][20][21][22][23][24][25]. Whether the altered liver expression occurs secondary to cholestasis remains unknown, while little is known about expression of MMPs and TIMPs after successful PE and clearance of jaundice.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, dysregulation of MMP14 has also been reported in both human and animal models of biliary atresia (Iordanskaia et al 2013). This suggests that the activation of TGFβ in the setting of biliary atresia may in part be mediated through both increased αvβ8 expression and altered expression of MMP14.…”
Section: Role Of Individual αV Integrins During Fibrogenesismentioning
confidence: 97%
“…Liver samples were homogenized according to the manufacturer's instructions in lysis buffer using homogenizer FastPrep-24 (MP Biomedicals). Subsequent manipulations were performed as described earlier (19). The concentration of murine CypA in plasma was determined using ELISA kits from MyBioSource following the manufacturer's instructions.…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%